Огляд методів контролю технічного стану ізоляції трьохжильних силових кабелів - Сизов, Євгеній Вікторович (Національний технічний університет "Харківський політехнічний інститут", 2025)
У статті розглянуто сучасні методи діагностики технічного стану ізоляції силових кабелів. Основну увагу приділено діелектричній спектроскопії в частотній та часовій областях, а також методам вимірювання ємності та тангенса кута діелектричних втрат у трьохжильних кабелях зі спільною металевою оболонкою. Наведено принципи прямих і сукупних вимірювань та результати обстеження силового кабелю після 24 років експлуатації на Хмельницькій атомній електростанції. Представлено результати аналізу, що дозволяють підвищити точність діагнос-тики ізоляції кабелів на основі вимірювання електричних параметрів їх ізоляції. This paper provides a comprehensive review of modern methods for assessing the technical condition of power cable insulation based on electrical diagnostic parameters. Special attention is paid to dielectric spectroscopy techniques in both the time and frequency domains, which allow for the identification of aging-related changes in insulation. The advantages and limitations of frequency-dependent diagnostics, including complex permittivity components and tgδ behavior, are considered. The study also presents methods for measuring capacitance and the dielectric loss tangent in three-core cables with a common metallic sheath, with detailed analysis of both direct and combined measurement configurations. The principles of interpreting partial and aggregate capacitances are discussed in the context of modeling insulation condition. In addition, the article addresses absorption-based diagnostic methods that rely on the measurement of polarization and depolarization currents and their relationship to the internal dielectric state.
Overview of methods for monitoring the technical condition of power cable insulation
Keywords: силовий кабель; діелектрична спектроскопія; тангенс кута діелектричних втрат; електрична ємність; діелектрична абсорбція; діагностика ізоляції; power cable; dielectric spectroscopy; dielectric dissipation factor; electrical capacitance; dielectric absorption; insulation diagnostics